Evaluating acne‐related post‐inflammatory hyperpigmentation is a challenge even amongst experts. Issue 12 (20th October 2014) - Goh, Chee Leok; Abad‐Casintahan, Flordeliz; Chow, Steven K. W.; Kubba, Raj; Miyachi, Yoshiki; Noppakun, Nopadon; See, JoAnn; Suh, Dae Hun; Xiang, Leihong Flora; Kang, Sewon; the Asian Acne Board
Abstract Post‐inflammatory hyperpigmentation (PIH) is a problematic and distressing acne sequela. The difficulty of clinically assessing and managing post‐inflammatory hyperpigmentation is especially prevalent in Asian populations. The Asian Acne Board conducted a study to evaluate concordance in diagnosis of post‐inflammatory hyperpigmentation in patients with active acne, acne scarring, and pigmentation problems. Seven dermatologists reviewed 64 anonymous clinical photographs projected onto a screen during a single session. Results showed that there were two groups of raters, those who found a high frequency of PIH and those who found a low frequency. There was significant variability in these two groups in rating the presence of PIH, with an average of 30 diagnoses (24%) difference between high‐ and low‐frequency raters. Results of severity ratings showed that while most cases of PIH were assessed as mild, there was marked variability between raters in their assessments of severity. Overall, variability in PIH diagnosis was greatest when active acne was present; in these cases, low PIH raters were more likely to report skin coloration as erythema instead of PIH. These findings uphold the importance of utilizing specific clinical criteria to improve accurate evaluation of skin color and we advocate future research into this area.